2006
DOI: 10.3998/ark.5550190.0008.713
|View full text |Cite
|
Sign up to set email alerts
|

Isocyanates in marine sponges: Axisocyanate-3, a new sesquiterpene from Acanthella cavernosa

Abstract: The isolation of axisocyanate-3 as a minor component of Acanthella cavernosa has been confirmed by spectroscopic characterisation of the metabolite, and by conversion of a mixture of axisothiocyanate-3 and axisocyanate-3 to their diethyl(thio)urea derivatives. The role of isocyanates in the formation of urea metabolites in sponges has been investigated through a model study with a menthyl-derived isocyanate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…575 A study of the terpenoid content of Acanthella cavernosa (E. coast, Australia) led to the isolation of 10-isothiocyanatoguai-6-ene 484 and 7-isocyano-7,8-dihydro-a-bisabolene 485, 576 while in a separate report, the same group described the isolation of axisocyanate-3 486 from the same sponge. 577 Two ethyl ethers, 11-ethoxy-3-formamidotheonellin 487 and 7-ethoxy-3-formamidobisabolane-8,10-diene 488, were obtained from Axinyssa aff. variabilis (Hainan, China); the authors suggested that they may be artifacts of solvolysis.…”
Section: Spongesmentioning
confidence: 99%
“…575 A study of the terpenoid content of Acanthella cavernosa (E. coast, Australia) led to the isolation of 10-isothiocyanatoguai-6-ene 484 and 7-isocyano-7,8-dihydro-a-bisabolene 485, 576 while in a separate report, the same group described the isolation of axisocyanate-3 486 from the same sponge. 577 Two ethyl ethers, 11-ethoxy-3-formamidotheonellin 487 and 7-ethoxy-3-formamidobisabolane-8,10-diene 488, were obtained from Axinyssa aff. variabilis (Hainan, China); the authors suggested that they may be artifacts of solvolysis.…”
Section: Spongesmentioning
confidence: 99%
“…Some siphonodictyals and corallidictyals have also been reported to have antimicrobial activity [ 28 , 29 ]. The other sponges from which compounds with antimicrobial activity have been isolated are Fasciospongia cavernosa [ 30 ] and Acanthella cavernosa [ 31 - 33 ]. A careful study of the previous literature showed that several compounds with AChEI activity, isolated from the sponges, mostly derivatives of alkaloids and terpenes [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Compared to the diterpenes, the larger group of marine isonitriles and related compounds contain a sesquiterpenoid backbone and are subdivided into nine classes. Similarly to the diterpene variants, these compounds are predominantly found in Bubarida, former members of Suberitida, and closely related species, e.g., [ 150 , 151 ] (see Figure 1 ), while several have also been described from unrelated taxa. These outliers comprise isonitriloids of the classes axanes, eudesmanes, aromadendranes, and epimaalianes, being reported from Axinella cannabina, e.g., [ 152 ], while unspecified Halichondria sp.…”
Section: Specificity and Phylogenetic Relevance Of Sponge Compoundsmentioning
confidence: 99%